Coalescence of co-infection and antimicrobial resistance with SARS-CoV-2 infection: The blues of post-COVID-19 world. (June 2021) - Mazumder, Payal; Kalamdhad, Ajay; Chaminda, GG Tushara; Kumar, Manish
Abstract: In viral respiratory infections, bacterial co-pathogens are widely known to co-infect, and they significantly increase the morbidity and mortality rate. During the influenza season, the advent of 2019-nCoV (novel coronavirus) has led to the widespread use of oral and intravenous antibiotics and inhibitors of neuraminidase enzyme. Owing to causes such as extended intubation, the ubiquitous use of intrusive catheters, and compromised host immunity, coronavirus disease (COVID-19) patients are at heightened risk of secondary bacterial and fungal infections, leading to the difficulty in their treatment. Apart from the pandemic, the primary risk is a likely surge in multidrug resistance. In this work, we evaluated the coalescence of present co-infection alongside the COVID-19 and post-pandemic antimicrobial resistance due to high ongoing drug use for the treatment of COVID-19. We found that while there is currently limited evidence of bacterial infections in COVID-19, available proof supports the restricted use of antibiotics from an antibiotic stewardship viewpoint, primarily upon entry. Paramount attempts should be made to collect sputum and blood culture samples as well as pneumococcal urinary antigen monitoring in order to endorse stringent antibiotic usage. For antimicrobial stewardship, inflammatory markers like procalcitonin have been added, but such biomarkers are typically upraised in COVID-19. Antimicrobials cannot be completely removed in wastewater treatment plants (WWTPs) and once they enter the water environment, possesses a great risk of inducing resistance to drugs in microbes. Hence, their prescription and administrations should be regulated and alternate solutions such as vaccines, preventive measures and personal hygiene should be given top priority. It is imperative to establish an antimicrobial strategy discrete to COVID-19, as this pandemic has caused an outbreak of numerous other associated diseases and has the potential to drive microbial resistance. Coordinated plans are essential for this at the citizen, health-care and policy levels.